2020
DOI: 10.12659/msm.924400
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Posterior and Anterolateral Surgical Approaches in the Treatment of Humeral Mid-Shaft Fractures: A Retrospective Study

Abstract: The aim of this study was to retrospectively assess and compare the functional outcomes and complications following anterolateral versus posterior surgical approaches for the treatment of mid-shaft fractures of the humerus. Material/Methods: This study included 107 patients treated for mid-shaft fractures between May 2015 and July 2018. Demographic and surgical data were collected for each patient. During follow-up visits, radiographs were acquired and evaluated. The clinical outcomes of the involved joints we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 40 publications
0
14
1
Order By: Relevance
“…The radial nerve and profunda brachii artery cross the posterior humerus obliquely from the medial to the lateral sides [ 6 8 ]. There is a chance of iatrogenic radial nerve injury in either the anterolateral or the posterior humeral shaft plating, with incidences of between 3.57% and 18.20% [ 9 11 ]. Previous studies have reported the incidence of radial nerve palsy in the anterolateral plating was similar to the posterior plating, but significantly higher only in one study [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The radial nerve and profunda brachii artery cross the posterior humerus obliquely from the medial to the lateral sides [ 6 8 ]. There is a chance of iatrogenic radial nerve injury in either the anterolateral or the posterior humeral shaft plating, with incidences of between 3.57% and 18.20% [ 9 11 ]. Previous studies have reported the incidence of radial nerve palsy in the anterolateral plating was similar to the posterior plating, but significantly higher only in one study [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the incidence of radial nerve palsy in the anterolateral plating was similar to the posterior plating, but significantly higher only in one study [ 4 ]. The posterior plating can endanger the radial nerve and/or profunda brachii artery by plate compression or accidental injury during surgical exposure while the anterolateral plating can injure the radial nerve and/or profunda brachii artery while drilling the screw holes and/or inserting the screws [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations